Pengungkapan Emisi Karbon pada Lima Sektor Prioritas dalam Net Zero Emissions - Juniati Gunawan; Zefanya Aulianisa Ganna Sumbun (MANAJEMEN, 2026)
This study aims to examine the level of carbon emission disclosure across five priority sectors in Indonesia in supporting the Net Zero Emissions (NZE) target, namely energy, waste, Industrial Processes and Product Use (IPPU), agriculture, and Forestry and Other Land Uses (FOLU). Using a qualitative approach, this study applies content analysis to annual and sustainability reports of companies listed on the Indonesia Stock Exchange during 2022-2024. The findings indicate that carbon emission disclosure remains uneven across sectors, with the energy and waste sectors showing relatively higher disclosure levels. Overall, disclosures are still largely narrative and policy-oriented, while quantitative consistency and accountability remain limited in supporting Indonesia’s NZE achievement.